The Impact of Mergers and Acquisitions on Financial Performance of Banks in the Kingdom of Bahrain during 2004-15 - Abdulwahab, Bushra A.; Ganguli, Subhadra (Information Management and Business Review, 2017)
Following the 2007 global financial crisis, more than 15 M&A transactions took place among financial institutions in the kingdom of Bahrain. This paper evaluates the impact of M&As on the financial performance of four such deals between banks in Bahrain. Data was collected from financial statements of the banks and the Bankscope database during 2004–2015. 15 accounting ratios were applied to CAMEL Rating Model approach. Financial modelling with Excel has been applied to test for the significance of changes in the financial performance of the banks three years before and three years after mergers. No significant difference in the financial performance of the local banks between pre and post M&As in the kingdom of Bahrain was observed. No significant difference in the financial performance of the acquirer bank or the target bank was observed except Bahraini Saudi Bank (target bank) which showed significant improvement in the financial performance after the merger with acquirer bank namely Al Salaam Bank. No significant change in the overall CAMEL ratios was observed for all banks involved in the M&As in Bahrain during 2004-15. The study provides an empirical analysis of the M&As before and after the mergers which can serve as a basis for further evaluation of future strategy of the banking sector in the kingdom of Bahrain.